2023
DOI: 10.1093/nar/gkad175
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterisation of Mer3 helicase interactions and the protection of meiotic recombination intermediates

Abstract: Crossing over between homologs is critical for the stable segregation of chromosomes during the first meiotic division. Saccharomyces cerevisiae Mer3 (HFM1 in mammals) is a SF2 helicase and member of the ZMM group of proteins, that facilitates the formation of the majority of crossovers during meiosis. Here, we describe the structural organisation of Mer3 and using AlphaFold modelling and XL-MS we further characterise the previously described interaction with Mlh1–Mlh2. We find that Mer3 also forms a previousl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Finally, streptavidin blotting revealed interesting information about the Mer3 helicase, whose function within the ZMM pathway is not fully understood (D uroc et al . 2017; A ltmannova et al . 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, streptavidin blotting revealed interesting information about the Mer3 helicase, whose function within the ZMM pathway is not fully understood (D uroc et al . 2017; A ltmannova et al . 2023).…”
Section: Discussionmentioning
confidence: 99%
“…However, another MLH complex, Mlh1-Mlh2, has been implicated in regulating both crossover and noncrossover associated gene conversion tracts in conjunction with the Mer3 helicase. Recent studies proposed that Mer3-Mlh1-Mlh2 limits gene conversion through the inhibition of the Pif1, a 5’-3’ DNA helicase known to stimulate Polδ strand displacement through its interaction with the DNA polymerase processivity clamp PCNA (Abdullah et al 2004; Wilson et al 2013; Buzovetsky et al 2017; Duroc et al 2017; Altmannova et al 2023). In support of this model, Vernekar et al (2021) found that Mer3 interacts with both Pif1 and Rfc1 in vivo and that the Mer3-Mlh1-Mlh2 complex blocks Polδ-mediated D-loop extension in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Mer3 is a helicase with many extra domains beyond its helicase core. It is most closely related to the spliceosomal RNA helicase Brr2 [ 11 , 125 ]. The helicase activity of Mer3 has been previously suggested to expand nascent D-loops, thus stabilising them.…”
Section: Zmm Proteins In Crossover Formationmentioning
confidence: 99%
“…The helicase activity of Mer3 has been previously suggested to expand nascent D-loops, thus stabilising them. Indeed, in vitro Mer3 clearly has a strong preference for D-loop DNA [ 11 , 126 ]. The preference for D-loop DNA binding suggests that Mer3 may bind to early recombination intermediates.…”
Section: Zmm Proteins In Crossover Formationmentioning
confidence: 99%
See 1 more Smart Citation